THE INFLUENCE OF GESTATIONAL DIABETES MELLITUS ON THE MORPHOFUNCTIONAL STATE OF PLACENTAS IN PATIENTS AFTER THE USE OF ASSISTED REPRODUCTIVE TECHNOLOGIES - Мурзин, Александр Викторович; Мелкозерова, Оксана Александровна; Чистякова, Гузель Нуховна; Гришкина, Анастасия Александровна (Mother and Baby in Kuzbass, 2024)
The effect of gestational diabetes mellitus (GSD) on the mother and fetus is determined by an increased risk of obstetric and perinatal complications. Pregnancy resulting from assisted reproductive technologies (ART) may also carry obstetric risks associated with the effect of hormonal stimulation on implantation processes and the formation of the uteroplacental complex. The pathogenetic mechanisms of the development of these pregnancy complications are associated with placental dysfunction, which manifests itself at different gestation periods and affects the development of complications. Purpose of the study – to study the pathomorphological features of placentas in patients with gestational diabetes mellitus, whose pregnancy occurred because of assisted reproductive technologies. Material and methods. A pathomorphological study of 86 placentas in women after ART was performed. The patients were divided into 2 study groups. Group I (main group) consisted of patients with GSD after ART (n = 45), group II (comparison group) – patients after ART without GSD (n = 41). The first group, depending on the presence or absence of perinatal complications of pregnancy, was divided into two subgroups: 1 – patients with perinatal complications (n = 29), 2 – patients without perinatal complications (n = 32). Depending on the type of ART programs, subgroups were identified: 3 patients who underwent an embryo transfer program (PE) in a cryoprotocol (n = 58) and 4 patients who underwent PE in a superovulation stimulation cycle (n = 29). All patients underwent a clinical and anamnestic assessment of pregnancy and childbirth, as well as a morphological examination of the placentas after delivery. Results. The patients of the study groups were comparable in age and anthropometric parameters (p > 0.05). The presence of a burdened obstetric and gynecological history (medical abortion, spontaneous miscarriage, non-developing pregnancy, p = 0.001) and extragenital diseases (pathology of the cardiovascular system (OR 3.84; 1.23–11.96; p = 0.003), hypothyroidism (OR 5.53; 1.42-21.29; p = 0.008), pathology of the urinary system (OR 4.96; 1.47-16.92; p = 0.007) was statistically significantly more often observed in patients of the main group. Morphological assessment of placentas in women after ART with GDM verified a significantly larger mass of placentas (p = 0.042), damage to the microstructure of the placenta in the form of vascular thrombosis (p = 0.033), signs of maternal malperfusion (p = 0.011).In patients after ART with the development of perinatal complications against the background of GDM, distal villous immaturity (p = 0.021), excessive fibrinoid deposition in the intervillous space (p = 0.047), compensatory formation of syncytial nodes (p = 0.034), a high incidence of maternal malperfusion (p = 0.011) and chronic basal deciduitis (p = 0.029). Microscopic examination of placentas in patients with PE in the superovulation stimulation cycle revealed a significantly higher frequency of fibrinoid deposition in the intervillous space (p = 0.044) with compensatory formation of syncytiotrophoblastic nodes (p = 0.044) compared to the cryotransfer group, and delayed villous maturation (p = 0.010), which was realized in the form of maternal and fetal malperfusion (p = 0.023), thrombosis of vessels in the intervillous space (p = 0.041), and was also accompanied by inflammatory changes in the decidual tissue (p = 0.029). Conclusion. There is a certain synergy regarding the effect of GDM and the use of ART methods on the morphofunctional state of the feto-placental complex, which may further increase the risks of obstetric and perinatal complications in this category of patients.